2010
DOI: 10.3947/ic.2010.42.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Current Usage and Prospect of New Antifungal agents in Korea

Abstract: The incidence of invasive fungal infections has been increased worldwide along with the increasing population at high risk for fungal infection. However, no data is available for the current status of usage of antifungal agents in Korea. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…We found that as members of the nonalbicans Candida species, the frequency of C. glabrata and C. krusei, known to be resistant to azoles, has increased from 11.3 to 16.3% and 0.5 to 1.7%, respectively, compared to previous studies (Jung et al, 2010;Lee et al, 2007). Although caspofungin was approved by the Korean Food and Drug Administration in 2001, there were cost-related barriers to its prescription because the total drug costs could not be covered by the national health insurance before the policy change (Kim and Kang, 2010). After the change in national health insurance coverage for newer antifungal agents, the patient's out-of-pocket share was reduced to 20% of the overall cost.…”
Section: Discussionmentioning
confidence: 99%
“…We found that as members of the nonalbicans Candida species, the frequency of C. glabrata and C. krusei, known to be resistant to azoles, has increased from 11.3 to 16.3% and 0.5 to 1.7%, respectively, compared to previous studies (Jung et al, 2010;Lee et al, 2007). Although caspofungin was approved by the Korean Food and Drug Administration in 2001, there were cost-related barriers to its prescription because the total drug costs could not be covered by the national health insurance before the policy change (Kim and Kang, 2010). After the change in national health insurance coverage for newer antifungal agents, the patient's out-of-pocket share was reduced to 20% of the overall cost.…”
Section: Discussionmentioning
confidence: 99%
“…The number of units consumed by each patient was multiplied by the cost per unit of each resource to estimate the direct costs for each patient. Since the four hospitals in the present study are rated as superior general hospitals in Korea, additional 30% of costs are charged for every resource provided (total costs ϭ the number of units consumed ϫ the unit cost ϫ (10), the use of these drugs as first-line agents in the treatment of invasive candidiasis or candidemia was limited due to their higher cost. Fluconazole or amphotericin B deoxycholate is admitted as first-line agents against Candida infection in Korea, and echinocandins admitted in the setting of treatment failure or toxicities of which criteria are defined by HIRA (health insurance review and assessment).…”
Section: Methodsmentioning
confidence: 99%
“…Although the 2009 guidelines for candidemia treatment by the Infectious Diseases Society of America recommend echinocandins as the first-line antifungal agents in the setting of neutropenia or moderate to severe illness (12), these drugs are not widely used worldwide as first-line agents due to their relatively high costs, especially in resource-limited countries (6,10). Fluconazole is still the most widely used drug, and amphotericin B deoxycholate is also frequently used for broader coverage of candidemia.…”
mentioning
confidence: 99%
“…To further explore the above factors, we decided to examine the global trends of three key variables: country-level data on healthcare antibiotic consumption (2000-2015) [85,86], antifungal consumption (2002-2018) [87][88][89][90], and the number of acute and long-term care beds (1980-2015) [91,92] in healthcare facilities. C. auris is known to afflict patients in acute and long-term care [51,81,82], however such patient populations are difficult to measure and their data are largely unavailable [93,94].…”
Section: Contrasting Geospatial Trends In Antimicrobial Usage and Host Populationsmentioning
confidence: 99%